Використання технологій штучного інтелекту для створення відео на основі тексту - Шатило, І. Ю.; Чала, Л. Е. (ХНУРЕ, 2025)
This paper introduces a technology designed for automated video generation from web-based articles. The system follows a structured process that includes content parsing, translating it, summarising key points, extracting keywords, and analysing sentiment. It selects relevant video clips and background music, synthesises voiceovers using text-to-speech technology, and assembles the final video. The result is a fully automated pipeline that converts textual content into dynamic video presentations, with applications in news automation, educational media, and digital content production.
Keywords: Концептуальна модель доповнення точкових хмар на основі графових нейронних мереж; створення відео